PENERAPAN MEDIA FLIPBOOK “KOMIK ZAMAN NOW” PADA PEMBELAJARAN SENI UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS IV SD - Karin Widya Ayuningtyas; Eka Titi Andaryani; Deni Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Fine arts learning in elementary schools often faces obstacles in fostering student creativity, especially in storytelling drawing (comic) materials. Conventional methods and the lack of interactive media cause students to have difficulty visualizing ideas and storylines, resulting in monotonous artwork. This study aims to analyze the effectiveness of implementing "Komik Zaman Now" Flipbook media in increasing the creativity of fourth-grade students. This study used a Mixed Method with a Sequential Explanatory design. The subjects were 27 fourth-grade students at SD Negeri Songgom 01. Data collection was carried out through performance tests (comic products), observations, and response questionnaires. Quantitative analysis results showed a significant increase in student creativity with an average N-Gain score of 0.72, which is in the high category. Qualitatively, digital flipbook media proved capable of creating an interactive learning atmosphere relevant to the students' world ("Zaman Now"), thereby triggering their visual and narrative imagination. It is concluded that the integration of flipbook-based digital comics is effective as an innovative solution in art learning in the digital era.